Stationary edge localized mode-free H-mode in ASDEX Upgrade. (6th April 2020) - Gil, L.; Silva, C.; Happel, T.; Birkenmeier, G.; Conway, G.D.; Guimarais, L.; Kallenbach, A.; Pütterich, T.; Santos, J.; Schneider, P.A.; Schubert, M.; Seliunin, E.; et al.
Abstract: A stationary H-mode without edge localized modes (ELMs) has been recently achieved in the ASDEX Upgrade tokamak by applying central electron cyclotron resonance heating above the L-H power threshold with adequate fueling. It is naturally obtained in favorable ∇ B configuration and has several features which are desirable for future reactors, such as dominant electron heating, low input torque, possibility of access at low input power, good energy confinement ( H 98 y 2 = 0.9 − 1.3 ), high density ( f G W = 0.8 − 0.9 ), and no impurity accumulation despite the absence of ELMs. This regime is similar to the EDA H-mode and always features an edge electromagnetic quasi-coherent mode which seems to be responsible for enhanced transport losses, as its appearance and disappearance are correlated with changes in edge and divertor parameters.